Effect of HRTs on COD and Nutrient Removal in Sequencing Batch Reactor (SBR) Process - Yea, Neo Kwang; Abdullah, Siti Rozaimah Sheikh; Ismail, Nur ‘Izzati; Sharuddin, Siti Shilatul Najwa (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
An effective wastewater treatment is a must to prevent water resources from being polluted. In this research, the method used was biological treatment with sequencing batch reactor (SBR) as the reactor to treatment synthetic wastewater. There were four stages involved in operation of SBR, which were fill, react, settle, and draw. Synthetic wastewater is being used as influent with C:N ratio = 500:50. Three hydraulic retention time (HRT)being tested, which were 24 h, 12 h, and 8 h. ORP, DO and pH were monitored online and its relationship with nutrient removal (ammonium, nitrate, nitrite, and phosphate) was observed. HRT 12 h and 8 h achieved similar performance among the three HRTs being tested while HRT 24 h achieved lowest percentage removal of nutrient.